Efeitos de compostos orgânicos de selênio sobre o desenvolvimento intra-uterino da prole de ratas wistar - Weis, Simone Nardin (2007)
Selenium (Se) is an essential trace element for man and is known for its role in regulating growth and development of the fetus and newborn. It is well known that Se deficiency is related to miscarriages and pre-term deliveries. However, it is established that Se compounds, depending of dose, can be highly toxic to several species of animals. The organoselenium compounds, diphenyl diselenide [(PhSe)2] and 3 3- ditrifluoromethyldiphenyl diselenide [(F3CPhSe)2] were the target of this study since they present important pharmacological properties. Therefore, it is necessary to dtudy the effects of these compounds on the embryofetal development. The purpose of the present study was to evaluate the effects of (PhSe)2 and (F3CPhSe)2 administration during the organogenesis period of intrauterine development of Wistar rats. Dams were subcutaneously exposed to (PhSe)2 (1.5, 3.0 or 6.0 mg/kg) or only vehicle (canola oil), from days 6 to 15 of gestation (Article). External and internal fetal examination was performed at gestational day 20. No mortality was observed in fetuses or dams at any (PhSe)2 treatment. A decrease in maternal body weight gain (corrected) was found in all (PhSe)2 groups and also an increase in the liver relative weight were observed in these dams, indicating maternal toxicity. Exposure to (PhSe)2 produced significant changes in fetal body weight and biometry. Furthermore, we verify an increase in the incidence of skeletal alterations of fetuses of all (PhSe)2 doses tested, however, these alterations were considered variations that are generally reversible and is unlikely to adversely affect survival or health. (PhSe)2 was capable to cause some morphological modifications on placentas such as vascular congestion, an increase in leucocyte infiltration and phagocytosis. These effects might have contributed with adverse reproductive outcomes observed in the progeny. In the second work presented in this dissertation (Manuscript), pregnant rats were given, via intragastric intubation, 1, 5 or 10 mg/kg of (F3CPhSe)2 or vehicle (canola oil), from days 6 to 15 of gestation. The parameters evaluated were the same of the first study. Administration of 5 and 10 mg/kg of (F3CPhSe)2 decreased maternal weight gain during pregnancy and this was accompanied by a reduced food consumption in the higher dose. Furthermore, there was an increase in liver absolute and relative weight of dams given the higher dose. These data confirm the liver as the primary target organ for Se compounds exposition. Differently from (PhSe)2 exposure, (F3CPhSe)2 administration did not alter fetal body weight and biometry. However, the compound caused embryolethality in the higher dose tested. This effect seems to be all or none since it led to totally resorption of some litters and the others were not affected by the compound. In this dose level, it was also observed a number of skeletal variations that, equally to (PhSe)2 study, seems unlikely represent survival risks. The placentas morphological analysis revealed that exposure to (F3CPhSe)2 was able to alter placental morphology. On the basis of results mentioned above, we conclude that maternal exposure to (PhSe)2 and (F3CPhSe)2 did not cause externally visible malformations but they were able to increase fetuses skeletal alterations incidence, without affecting fetuses survival. Organoselenium compounds also alter placental morphology that could contribute with adverse reproductive outcomes observed on the progeny.